PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP STRUKTUR MODAL DI INDONESIA - Anggraini, Rista; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the influence of corporate governance mechanisms such as board of commissioner, institutional ownership, governmental ownership, and quality of external auditor on firm’s capital structure in Indonesia. This study also uses three control variables such as growth opportunity, profitability, and firm size. The population in this study consists of all listed non- financial firms in Indonesia Stock Exchange (BEI) in year 2013. The sampling method used in this study is purposive sampling with specified criteria. By doing sampling and processing data, the final amounts of the sample are 398 firms. This study uses multiple regression analysis technique to examine the hypotheses. The results of this study show that board of commissioner has negatively significant influenced on capital structure. Institutional ownership and governmental ownership are not significantly affected on capital structure. Quality of external auditor has negatively significant influenced on capital structure, but independent sample t-test about quality of external auditor shows that actually there is no difference on capital structure between firms engaging with the Big Four audit firms and  firms engaging with the non-Big Four audit firms.